2020
DOI: 10.1111/jcmm.14951
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of bile acid profile by gut microbiota in chronic hepatitis B

Abstract: Chronic hepatitis B (CHB) is a global epidemic disease that may progress to fibrosis, cirrhosis and hepatocellular carcinoma. The role of the liver‐bile acid‐microbiota axis in CHB remains unclear. The aims of this study are to elucidate the alteration of the gut microbiota and its functions in bile acid homeostasis in CHB patients with different degrees of fibrosis. In the present study, we evaluated serum and faecal bile acid profiles in healthy controls and CHB patients with biopsy‐proven diagnosis: patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 29 publications
(82 reference statements)
5
51
0
Order By: Relevance
“…In addition, a lower fecal DCA/CDCA ratio has been suggested to reflect the activation of FXR in the ileum. [ 30 ] Consistently, the upregulated fecal CDCA and downregulated fecal DCA/CDCA ratio in the WC group could activate ileal FXR, which induced FGF15 secretion, as evidenced by the higher serum FGF15 concentration in this study. Interestingly, FGF15 deficiency has been confirmed to alleviate CCL 4 ‐induced liver fibrosis by activating CTGF, which results in the activation of hepatic stellate cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, a lower fecal DCA/CDCA ratio has been suggested to reflect the activation of FXR in the ileum. [ 30 ] Consistently, the upregulated fecal CDCA and downregulated fecal DCA/CDCA ratio in the WC group could activate ileal FXR, which induced FGF15 secretion, as evidenced by the higher serum FGF15 concentration in this study. Interestingly, FGF15 deficiency has been confirmed to alleviate CCL 4 ‐induced liver fibrosis by activating CTGF, which results in the activation of hepatic stellate cells.…”
Section: Discussionsupporting
confidence: 76%
“…The ratio of DCA to CDCA is thought to reflect the activation of FXR, which influences the secretion of FGF19 (FGF 15 is the mouse ortholog). [ 30 ] In our study, a decreased ratio of DCA to CDCA was observed in CCL 4 + WD‐treated mice (Figure 8F, CC vs WC p < 0.05). To verify our results, we detected the serum levels of FGF15 and found that they were upregulated dramatically in the WC group, which was consistent with the change in the ratio of DCA to CDCA (Figure 8G).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…17,44 BAs represent a crucial partaker in liver-microbiota communication, and their composition and concentration seem to have a positive correlation with metabolism and hepatic fibrosis. 45,46 The composition of BAs is important in many metabolic diseases, it has been described that patients with T2DM present a change from PBA to SBA with an increase in deoxycholic acid levels. BAs are metabolic integrators that act through signaling pathways that regulate the expression of certain metabolic genes; hence, a tweak in BA signaling might promote and aggravate metabolic syndrome.…”
Section: Ba Compositionmentioning
confidence: 99%
“…Bile acid acyl-CoA-synthetase (BACS), which catalyzes taurine conjugation in BAs in the liver and apical bile acid transporters in the ileum, were downregulated in CONV-R mice ( 53 ). In a human study for chronic hepatitis B, the levels of total and primary BAs (TCDCA, GCDCA, GCA, and TCA) were upregulated in hepatitis B patients with moderate/advanced fibrosis, accompanied with downregulation of gut microbiota (such as Bacteroides and Ruminococcus) responsible for BAs metabolism ( 54 ). Trimethylamine N-oxide (TMAO), which is a metabolite produced by gut microbiota from choline, stimulated the expression of CYP7A1 in the liver, increased the serum levels of BAs and promoted FXR-antagonistic BAs ( 55 ).…”
Section: Gut Microbiota and Liver Pathophysiologymentioning
confidence: 99%